Bupivacaine 0.5% vs. levobupivacaine 0.5% for epidural anaesthesia for caesarean section: a comparative study - Pahuja, Heena D.; Tajne, Megha P.; Bhure, Anjali R.; Chauhan, Savita M. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Levobupivacaine has been purported to be as efficacious as Bupivacaine for epidural anaesthesia in recent literature. Methods: With the intent to study the same in caesarean section cases in our set up, we observed various intra- and post-operative variables in two groups (Levobupivacaine and Bupivacaine) of 60 healthy parturients. Sixty parturients for elective caesarean section were allocated randomly to receive epidural block with 10-20 ml of either 0.5% Levobupivacaine with Fentanyl 25µg or 0.5% Bupivacaine with Fentanyl 25µg to reach T6 level. Results: Mean total volume in Bupivacaine group was 15.23ml and in Levobupivacaine group was 12.76 ml. The difference was statistically significant. There was significant difference between the groups in the sensory block. The onset of analgesia was earlier in Levobupivacaine group. Mean time was 6.20 minutes in Bupivacaine group and 4.36 minutes in Levobupivacaine group. The duration of motor block was significantly short in Levobupivacaine group. Mean Time for recovery from motor block in Bupivacaine group was 2.5 hours and in Levobupivacaine group 1.5 hours. Mean time to achieve T6 height was earlier in Levobupivacaine group i.e. 16.46 minutes in Bupivacaine group and 13.26 minutes in Levobupivacaine group. Duration of postoperative analgesia was similar. There was no significant difference in neonatal outcome. Conclusions: Levobupivacaine was found to fare better than Bupivacaine in the studied intra and post-operative parameters and is hence recommended over racemic Bupivacaine for epidural block in patients undergoing elective cesarean section.